US Rowing (2008)
Rowing is one of the original sports in the modern Olympic Games. Baron Pierre de Coubertin, founder of the modern Olympics, was a rower. Rowers were the third largest U.S. delegation (48 athletes) to the Olympic Games in 2000. On July 19, 2008, the organizational members of USRowing will be asked to approve significant changes in the organization`s governing documents. The proposed changes were developed over the last four years through a process that involved people from all areas of rowing. The driving factors behind the new governance documents are to: * Meet the requirements of the Ted Stevens Olympic and Amateur Sport Act; and * Make USRowing`s governance a model of non-profit organizations best practices. The process also was guided by the desire to simplify and remove the inconsistencies in the governing documents and comply with all of the legal requirements of being a non-profit incorporated in Pennsylvania.